2007
DOI: 10.1111/j.1365-2044.2007.05260.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of intranasal midazolam in the treatment of paediatric dental patients*

Abstract: SummaryThe aim of this study was to assess the use of intranasal midazolam in paediatric dental patients requiring extractions or simple surgical procedures who may otherwise have required a general anaesthetic. Twenty children aged between 2–9 years who required simple surgical procedures were given 0.25 mg.kg−1 midazolam, administered using a MAD® (Mucosal Atomization Device; Wolfe Tory Medical Inc., Salt Lake City, UT, USA). Compliance with the full dose was achieved in 14 patients, 13 of whom completed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 13 publications
1
20
0
Order By: Relevance
“…Midazolam was selected for use in the INS route because it provides some degree of amnesia, it has a short duration of action, and its sedative effect can be quickly and easily reversed. 8 The amnestic property of midazolam allows the child to forget about the unpleasant experience so as to allow future dental treatment to be a positive experience, thereby allowing the child to achieve improved oral health. 9 We did not study amnesia, but amnesia is a common effect of midazolam.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Midazolam was selected for use in the INS route because it provides some degree of amnesia, it has a short duration of action, and its sedative effect can be quickly and easily reversed. 8 The amnestic property of midazolam allows the child to forget about the unpleasant experience so as to allow future dental treatment to be a positive experience, thereby allowing the child to achieve improved oral health. 9 We did not study amnesia, but amnesia is a common effect of midazolam.…”
Section: Discussionmentioning
confidence: 99%
“…9 We did not study amnesia, but amnesia is a common effect of midazolam. 8 Amnesia is preferable in young children undergoing unpleasant procedures such as dental extractions, as most extremely anxious children experience psychological trauma in their first dental appointment. 8,10 The level of sedation among children varied after INS administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We wish to congratulate Gilchrist et al for their recent publication [1]. We agree on the efficacy and safety of midazolam in children having procedures who may otherwise have required a general anaesthetic.…”
mentioning
confidence: 85%
“…We believe that in the case of therapeutic hypothermia, where two such trials have been reported, we have a responsibility to embrace this therapy [1,2]. This does not mean that the evidence is overwhelming.…”
Section: A Replymentioning
confidence: 99%